A novel way to understand and communicate the burden of AntiPsycHotic prescribing for adults across specialist Intellectual Disability services in England and Wales: the APHID feasibility study protocol - Emily Stanyard; Helen Neilens; Victoria Allgar; Victoria Allgar; Matthew Bailey; Crispin Musicha; Kiran Purandare; Bhathika Perera; Ashok Roy; Indermeet Sawhney; Lance Watkins; Lance Watkins; et al. (Frontiers in Health Services)
BackgroundThe stopping overmedication of people with a learning disability, autism, or both (STOMP) programme was launched in 2016 in response to concerns about the over-prescribing of medication in people with intellectual disability. The programmes focus has been on the withdrawal of antipsychotic treatment for the individual person than the service or dosage optimisation. It could be that cumulative service level antipsychotic treatment converted and presented as chlorpromazine units could allow for comparison of services on how antipsychotic treatment is being utilised and allow for comparing of practices between services in different regions. The aim of this feasibility study is to explore if cumulative service scores of antipsychotic treatment burden could define prescribing patterns across different specialist intellectual disability services in England and Wales, focused on those on ≥2 antipsychotic treatments. There is no evidence to use ≥2 antipsychotic treatments for any individual.MethodsThe study is a feasibility cross-sectional study investigating service antipsychotic treatment cumulative burden at seven annual time points, 2017–2023. De-identified data for adult patients with intellectual disability under the care of specialist intellectual disability services in receipt of ≥2 oral and/or long-acting IM (intramuscular) injectable (depot) antipsychotic treatments are included. Demographic and clinical data will be collated, in addition to information on the prescribed antipsychotic treatments. The data will be evaluated for data completeness and will be inputted into the Statistical Process Control tool. Outcomes will be measured using a combination of methods including descriptive analysis (including mean, standard deviation and percentage values), and a mixed effects regression model, to determine changes in chlorpromazine equivalent dose values over time.ResultsSeven England and Wales National Health Service intellectual disability services are recruiting up to 490 people. There were recognised challenges in identifying the relevant eligible cohort across services and administering a common set of outcome measures.DiscussionThis study is intended to inform decisions to design a wider registry that would involve antipsychotic treatment prescribing data for patients across multiple sites nationwide. Developing a de-identified database using routinely collected data, without the requirement for informed consent, comes with unique benefits and challenges.Registry referenceNCT06238089 (www.clinicaltrials.gov).